European patch test results with audit allergens as candidates for inclusion in the European Baseline Series, 2019/20: Joint results of the ESSCAA and the EBSB working groups of the ESCD, and the GEIDACC. (17th February 2022) - Uter, Wolfgang; Wilkinson, S. Mark; Aerts, Olivier; Bauer, Andrea; Borrego, Leopoldo; Buhl, Timo; Cooper, Susan M.; Dickel, Heinrich; Gallo, Rosella; Giménez‐Arnau, Ana M.; John, Swen M.; Navarini, Alexander A.; et al.
Abstract: Background: In 2019, a number of allergens (haptens), henceforth, "the audit allergens, " were considered as potential additions to the European Baseline Series (EBS), namely, sodium metabisulfite, 2‐bromo‐2‐nitropropane‐1, 3‐diol, diazolidinyl urea, imidazolidinyl urea, Compositae mix II (2.5% or 5% pet), linalool hydroperoxides (lin‐OOH), limonene hydroperoxides (lim‐OOH), benzisothiazolinone (BIT), octylisothiazolinone (OIT), decyl glucoside, and lauryl glucoside; Evernia furfuracea (tree moss), was additionally tested by some departments as well. Objectives: To collect further data on patch test reactivity and clinical relevance of the audit allergens in consecutive patients across Europe. Methods: Patch test data covering the audit allergens in 2019 and 2020 were collected by those departments of the European Surveillance System on Contact Allergies testing these, as well as further collaborators from the EBS working group of the European Society of Contact Dermatitis (ESCD), and the Spanish Grupo Español de Investigación en Dermatitis de Contacto y Alergia Cutánea. As patch test outcome, reactions between day (D) 3 and D5 were considered. Results: Altogether n  = 12 403 patients were tested with any of the audit allergen. Positive reactions were most common to lin‐OOH 1% pet. (8.74% [95%CI: 8.14–9.37%]), followed by lin‐OOH 0.5% pet., and lim‐OOH 0.3% pet (5.41% [95% CI: 4.95–5.89%]). Beyond these terpene hydroperoxides, BIT 0.1% pet. was the second most common allergen with 4.72% (95% CI: 4.2–5.28%), followed by sodium metabisulfite 1% pet. (3.75% [95%CI: 3.32–4.23%]) and Compositae mix 5% pet. (2.31% [95% CI: 1.84–2.87%]). For some allergens, clinical relevance was frequently difficult to ascertain. Conclusions: Despite many positive patch test reactions, it remains controversial whether lin‐ and lim‐OOH should be tested routinely, while at least the two preservatives BIT and sodium metabisulfite appear suitable. The present results are a basis for further discussion and ultimately decision on their implementation into routine testing among the ESCD members. Highlights: Twelve preservatives, fragrances, and emulsifiers were evaluated as potential additions to the European Baseline Series (EBS) The highest prevalences of positive reactions were to linalool hydroperoxides 1% pet. or 0.5% pet. and limonene hydroperoxides 0.3% pet. Benzisothiazolinone 0.1% pet. was positive in 4.7%, followed by sodium metabisulfite 1% pet. (3.8%) and Compositae mix 5% pet. (2.3%). The results are a basis for further discussion and ultimately a decision on their implementation into routine testing among the European Society of Contact Dermatitis (ESCD) members.